P14.28 First report on the combination of axitinib and Tumor Treating Fields (TTFields) in three patients with recurrent glioblastoma. (6th September 2019) - Keßler, A F; Weiland, J; Linsenmann, T; Ernestus, R; Hagemann, C; Löhr, M
Abstract: BACKGROUND: Adding Tumor Treating Fields (TTFields) to first-line therapy in glioblastoma (GBM) demonstrated significantly improved survival in the EF-14 trial. Furthermore, in a post-hoc analysis of the EF-14 trial, median overall survival increased significantly upon recurrence (rGBM) for patients treated with bevacizumab (Bev) and TTFields compared to Bev monotherapy. Axitinib (Axi) is an orally available tyrosine kinase inhibitor which is approved for the treatment of metastatic renal cell carcinoma. It has a high affinity and specificity for vascular endothelial growth factor receptors, thereby acting similar to Bev. In phase 2 trials, Axi improved response rate and progression free survival in rGBM patients compared to historical controls with a manageable toxicity profile. We report on three rGBM patients treated with TTFields and Axi (AxiTTFields). METHODS: A 53-year-old male patient (#1) presented with a multifocal and consistently progressing GBM after initial surgery, radiochemotherapy (RCT) and after 4 cycles of temozolomide (TMZ), combined with TTFields. To meet the urgent need of an alternative treatment, Axi (5mg twice a day) was added to the treatment regimen. In a 46-year-old male patient (#2), an early progress occurred after surgery, RCT and 3 cycles of TMZ combined with TTFields. Similarly to #1, Axi was added to the treatment regimen. In a 61-year-old male patient (#3) with a rGBM after surgery and RCT at the time of the 6 th cycle of TMZ, TTFields therapy was initiated at recurrence and treatment regimen was adapted to AxiTTFields. RESULTS: In these three patients, AxiTTFields was safe and feasible. #1 and #2 were on AxiTTFields therapy for more than 8 months, presenting an improved neurological status with a partial response in the MRI 3 months initiating the combined treatment of AxiTTFields. #3 declined in his neurological status without any change in the MRI monitoring and died 2.4 months after initiating AxiTTFields. Although, Axi as well as TTFields may cause skin irritations, none were observed in this case series. With an average of 77 % in these three patients, the TTFields usage rate was above the independent prognostic threshold of 75 %, underlining the feasibility of this approach. There were no additional adverse events due to the combined therapy of AxiTTFields. CONCLUSION: In summary, AxiTTFields was feasible and safe in three rGBM patients. As the addition of Axi to TTFields therapy is a promising approach, we plan to investigate the safety and feasibility of this combination in a pilot trial. Further studies might explore effects on outcome and survival of AxiTTFields in rGBM.